Librarian-academic collaboration: the role of strategic communication and relationship management - Marlene Wiggil (Communicare)
Information literacy and critical thinking skills are essential in the information age towards achieving academic success and being adequately skilled for lifelong learning. Academic libraries have an indispensable role to play in this regard. Collaboration between librarians and academics is important to ensure both effective information-literacy training and service provision to students and to the academic community. However, a lack of understanding, knowledge, and communication regarding academic libraries’ teaching and research role is proving to be an obstacle in obtaining librarian-academic collaboration. Academic libraries do mostly not apply strategic communication management to build and maintain relationships with its stakeholders, which contributes to the challenges surrounding librarian-academic collaboration. This paper reports on how four academic libraries practise communication and relationship management to enhance librarian-academic collaboration. The study aims to make recommendations for the application of more effective, strategy-driven communication and relationship management to enhance librarian-academic collaboration.